Coagulantes orgânicos no tratamento da manipueira de fecularia de mandioca - Botelho, André Campos Colares (2019)
The manioc (Manihot esculenta Crantz) industrial processing generate numerous quantities of residues that cause seriously problems. The manipueira, wastewater, is constituted of the blend of extracted water by the industry with the liquid of the root formation, that contains high concentration of organic material and cyanidric acid. The coagulation/flocculation is a practice of chemistry clarification that involves the usage of chemistry products to remove, by precipitation, the impurites of the water or the effluent. The naturals coagulants present advantages in relation of the chemicals for being reliable, generally free from toxic substances, generate a smaller volume of sludge, low cost and do not be corrosive. The coagulants of TANFLOC® and ACQUAPOL® line are originated essentially vegetal, removed from the tree bark Acacia mearnsii. In this reguard, the objective of this work was to propouse an alternayive treatmant of the effluent starch of the manioc in relation to the conventionals processes, studying its treatability by chemistry clarification like the mainly treatment with the organic coagulants/flocculants of line TANFLOC® SG and SH and the ACQUAPOL® T-832 and Plus in comparison with the PAC. The effluent was collected in a starch of manioc localizated in the city of Candido Mota (SP). A fractional factorial planning 24-1 with central point was executed to determinated if the pH variables, coagulants concentration, velocity and time of the mixed affect in the process of chemistry clarification. By the obtained results, delineated a rotating central compost planning, evaluating the reducing of turbidity. The statistics analysis of the planning demonstrated that the pH and the coagulants concentration were the variables of most importance in the reaction. It validated the results by an experimental testing in the optimized conditions and it compareted the results of this experiment with the predicted results through the determinated models. The coagulants that gave the best response to the treatment were: ACQUAPOL® T-832 (turbidity, chemical oxygen demand and biochemical oxygen demand), followed by ACQUAPOL® Plus (lower Artemia salina ecotoxicity, higher reduction of total dissolved solids and high decantation velocity). TANFLOC® SG was the most balanced coagulant among them. The PAC was very efficient in reducing the biochemical oxygen and turbidity, but showed high Artemia salina ecotoxicity and inadequate reduction of chemical oxygen demand, total dissolved solids and decantation velocity after treatment of the wastewater. Several of this coagulants can be used as maily treatment or even preliminar the manner of reduce the maximum the organic load to be launched in the others treatment levels.